Blast-resistant framing system. (Architectural Record, 2008)
The article profiles the Reliance blast resistant framing system which is manufactured by Vistawall of Terrell, Texas. A discussion of the features of the framing system, which meets the increased security requirements of government and academic buildings with a pressure glazed curtain-wall system, is presented.